Addition of Maltodextrin Concentration to Anthocyanin Characteristics and Levels in the Manufacture of Natural Dyes from the Skin of Red Dragon Fruit (Hylocereus polyrhizus) - Eka Herlina; Diana Widiastuti; Fatwa Rachmawati Annissa (Universitas Pakuan, 2021)
Synthetic dyes in food products can cause health problems, making some people reduce such products' consumption. Alternatively, instead of avoiding consumption, people can do better by switching to natural dyes in food processing. One possible solution is to use the red dragon fruit's skin (hylocereus polyrhizus), containing anthocyanin pigments of the cyanidin-3-glucoside type. The purpose of this study is to propose the use of red dragon fruit's skin as a natural dye and to determine the characteristics, anthocyanin levels, and shelf life of red dragon fruit peel dye. The making of red dragon fruit peel dye was done by first extracting it with a maceration technique. After that, maltodextrin was added to the filtrate while the drying temperature was carried out at 28°C and 13°C. The results showed that natural dyes with a concentration of 30% maltodextrin at 13° C were the selected dyes and had the best characteristics. The total yield analysis resulted was 11.30%; pH measurement of 4.24; water content of 1.03%; solubility of 98.08%; color intensity L value of 59.41; a value of 33.44; and the b value of -7.78. The results obtained from the analysis of anthocyanin levels were 15.0290 ppm. The total plate number test obtained is 2.1 x 102 colonies/gram with a storage life of 282 days.